Socio-economic Research in Personnel versus Personnel Economics. Issue 1 (2nd January 2017) - Nienhueser, Werner
Abstract : This paper argues that personnel economics is still dominated by the assumptions of orthodox microeconomics, and also that newer fields such as transaction cost theory are far removed from socio-economics. Personnel economics is characterised by assumptions of unbounded rationality, stable preferences and functioning markets; power differences are seen as unimportant for explanations. By contrast, a socio-economic perspective works with the assumption of bounded rationality; it takes preferences into account, assumes that markets are characterised by 'non-equilibrium' states and power differences. The paper outlines a socio-economic mode of explanation and suggests that any explanation should include assumptions about three theoretical mechanisms: pursuit of utility, power and sense-making.